Electronic health record standards, coding systems, frameworks, and infrastructures - Sinha, Pradeep K.; Sunder, Gaur; Bendale, Prashant; Mantri, Manisha; Dande, Atreya (IEEE Press/John Wiley & Sons, 2013)
The book offers most comprehensive coverage of available EHR (Electronic Health Record) Standards including ISO, European Union Standards, and national initiatives by Sweden, Netherlands, Canada, Australia and many others"--Provided by publisher